Predictors of Depression after Stroke - Maree L. Hackett; Craig S. Anderson (2005)
Background and Purpose— Although depression is common after stroke, there is uncertainty over its etiology and risk factors, which complicates management. Knowledge of the predictors of depression associated with stroke may allow for the better targeting of therapy, both prevention and treatment. Methods— We undertook a systematic review of all published, nonexperimental, population-, hospital-, and rehabilitation-based stroke studies (to June 2004) with prospective, consecutive patient recruitment undertaken to identify variables associated with depressive symptoms (or “illness”) after stroke. Assessments were made of the quality of studies including the validity of prognostic models. Results— Data were available from 3 population-based studies including 492 patients, 8 hospital-based studies including 15 272 patients, and 9 rehabilitation-based studies including 2170 patients. Physical disability, stroke severity and cognitive impairment were consistently associated with depression. In addition to the common problem of selection bias, major limitations of these studies included variable selection and poor statistical quality and reporting; small sample sizes meant that only a limited range of variables were analyzed in multivariate models. Conclusions— There is a paucity of well-designed studies of sufficient size to allow stable multivariate predictive models of depression after stroke to be developed. Other than showing that depression is associated with more severe strokes, current evidence does not allow for ready identification of patients most at risk of developing this important complication of stroke.